Dolichopoda cave crickets from Peloponnese (Orthoptera, Rhaphidophoridae): molecular and morphological investigations reveal four new species for Greece. Issue 1 (1st January 2021) - Allegrucci, G.; Rampini, M.; Chimenti, C.; Alexiou, S.; Di Russo, C.
Abstract: Three species belonging to the genus Dolichopoda (Orthoptera; Rhaphidopohoridae) are known so far from the Peloponnese, all endemic to the area. In particular, D. matsakisi is known from two mountains in the North, while D. dalensi is present in the east region. The third species, D. unicolor, is distributed in the southern part of the Peloponnese, inhabiting caves on Mt Taygetos and Mani Peninsula. Recently, extensive sampling work in most of the Peloponnese has led to the discovery of new taxa, morphologically differentiated by the above three known species. To investigate the delimitation of the Peloponnesian species of Dolichopoda, we performed both morphological and molecular analyses. Morphological analysis was carried out by considering diagnostic characters generally used to distinguish different taxa, as the shape of epiphallus in males and the subgenital plate in females. Molecular analysis was performed by sequencing three mitochondrial genes, 12S rRNA, 16S rRNA, and COI, and one nuclear gene, 28S rRNA. Results from both morphological and molecular analyses were used to revise the taxonomic arrangement of the Peloponnesian species. On the whole, we were able to distinguish seven lineages of Peloponnesian Dolichopoda species, of which D. kofinasi n.sp., D.epidavrii n.sp., D. poseidonica n.sp., and D. propanti n.sp. are described as new species. http://www.zoobank.org/urn:lsid:zoobank.org:pub:857875CB-22B9-4CFC-9B7F-3FDDFC47A4E6